Mobile Packet Internet Groper (Moping) Application and Database Connection for Testing the QoS of Internet Services - Edy Budiman; Ummul Hairah (International Journal of Computing and Informatics (IJCANDI), 2016)
Optimizing the Quality of Experience (QoE) of mobile applications over cellular networks requires detailed knowledge of the underlying network and it is performance. Parameters of interest are, besides the signal strength and availability of technologies, the Round-trip Time (RTT) and available throughput of individual cells at a given location. This information is generally not readily available. Therefore, an Android application measuring the cellular network performance was developed. This demonstration shows the Mobile Ping (Moping) Network App, being implemented to provide visual feedback of the measured network quality to the users. The Mobile Packet Internet Groper (Moping) enables mobile application developers to characterize the data delivery performance of cellular data networks as delivered to mobile devices. Mobile application developers need to know a range of network performance characteristics, including latency, jitter, throughput, and network timeout delays. Of particular importance is how these values vary in different network provider, network technology, and mobile device combinations. To enable data collection from users across the range of technologies available, the application of Moping offers a lightweight measurement architecture that can be deployed on a wide range of Android-enabled mobile devices. The essential effect of mobile systems is that link quality becomes extremely variable, often in a random manner, although some parts of this effect can be predicted, or statistically modelled. The main QoS parameters – reliability of connection, bandwidth, latency and jitter are all affected by mobility, both during and between connections.